Problem-solving training to improve caregiver burden and depressive symptoms among dementia caregivers: personal and clinical factors of responders vs. non-responders - Juengst, Shannon B.; Smith, Matthew Lee; Wilmoth, Kristin; Wright, Brittany; Han, Gang; Supnet, Charlene; Maestre, Gladys (Frontiers in Public Health, 2025)
IntroductionMetacognitive strategy training interventions, like Problem-Solving Training/Descubriendo Soluciones Juntos (PST/DSJ), have efficacy for improving caregiver burden and depressive symptoms. We previously demonstrated that PST/DSJ improved caregiver burden and depressive symptoms among caregivers of adults with Alzheimer’s Disease and related dementias (ADRD), regardless of the number of sessions or boosters received. However, these results did not examine factors characterizing those who responded (improvement in caregiver burden or depressive symptoms) or did not respond to the intervention.ObjectiveTo identify key personal and clinical factors associated with response to PST/DSJ. Personal factors included age, gender, race, Hispanic ethnicity, education, and employment status. Clinical factors included care recipient diagnosis and dementia severity, caregiver problem-solving skills at baseline, caregiving experiences (caregiver life social support, satisfaction and resentment with the caregiving role, anger toward the care recipient, and care recipient aggressive, depressive, and forgetful behaviors), and social disconnection, caregiver burden, and depressive symptoms.MethodWe conducted a 2 × 2 randomized controlled optimization trial to test remotely delivered PST/DSJ to ADRD caregivers (NCT04748666). Primary outcomes were caregiver burden, measured by the Zarit Burden Interview (ZBI), and depressive symptoms, measured by the Patient Health Questionnaire-8 (PHQ-8). Response to PST/DSJ was defined for each primary outcome as a clinically important change (defined as ≥1 point on ZBI and ≥3 on PHQ) from baseline to 6-month follow-up.ResultsNinety-one caregivers were included in responder analysis, with 55 (60.4%) demonstrating a clinically meaningful improvement in caregiver burden and/or depressive symptoms. No personal factors were associated with being a Responder (vs. Non-Responder). Clinical factors associated with being a Responder were greater care recipient dementia severity (FAST score, p < 0.01), lower baseline caregiver life satisfaction (p = 0.05), higher baseline caregiver overload (p = 0.05), higher baseline caregiver burden (p = 0.01), and more baseline depressive symptoms (p < 0.01).ConclusionMost caregivers demonstrated a clinically meaningful improvement in caregiver burden and/or depressive symptoms after receiving PST/DSJ. Notably, those who responded had higher symptoms of distress, including caregiver burden and overload and depressive symptoms and lower life satisfaction, and had care recipients with more severe dementia, indicating that those benefiting from the intervention were those most in need of this support.Clinical trial registrationClinicalTrials.gov, identifier is NCT04748666.